Arab-related bilateral and multilateral sources of development finance: Issues, trends, and the way forward - Eric Neumayer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This article analyses the organizational structure as well as the characteristics of development finance provided by Arab donor countries. This is done with a comparative view in relation to western donors and with the aim to develop recommendations as to how Arab development finance can be strengthened and rendered more effective for the new Millennium. In the 1960s and 1970s Arab donors established a variety of national and multilateral agencies. These agencies share many characteristics of their western counterparts, but some also exhibit distinctive features. Both in terms of absolute volume as well as generosity measured by aid as a percentage of GDP, Arab countries have been important donors in the past, even though recent years have seen a significant fall in Arab aid. Reversing this downfall in aid, targeting its aid better towards the poor and very poor recipient countries and raising the grant share and the concessionality of loans for these countries together with a reallocation of aid towards the social sectors of human development would render Arab aid-giving more effective in terms of poverty alleviation and more in line with western aid. A greater willingness to participate in the ongoing discussions amongst western donors about the proper objectives and design of development finance would help Arab donors to achieve the recognition they truly deserve. Closer cooperation with western donors would be a logical consequence of taking such a step. However, this would also need to be matched by a greater willingness on the part of western donors to take their Arab counterparts seriously as partners of development finance. – aid ; official development assistance ; Arab agencies ; Development Assistance Committee
Keywords: F34; F35; 330; Entwicklungshilfe; Entwicklungsfinanzierung; Entwicklungskooperation; Arabische Staaten